The effect of cognitive aging on implicit sequence learning and dual tasking - Vandenbossche, Jochen; Coomans, Daphné; Homblé, Koen; Deroost, Natacha (Frontiers in Psychology, 2014)
We investigated the influence of attentional demands on sequence-specific learning by means of the serial reaction time (SRT) task (Nissen & Bullemer, 1987) in young (age 18-25) and aged (age 55-75) adults. Participants had to respond as fast as possible to a stimulus presented in one of four horizontal locations by pressing a key corresponding to the spatial position of the stimulus. During the training phase sequential blocks were accompanied by (1) no secondary task (single), (2) a secondary tone counting task (dual tone), or (3) a secondary shape counting task (dual shape). Both secondary tasks were administered to investigate whether low and high interference tasks interact with implicit learning and age. The testing phase, under baseline single condition, was implemented to assess differences in sequence-specific learning between young and aged adults. Results indicate that (1) aged subjects show less sequence learning compared to young adults, (2) young participants show similar implicit learning effects under both single and dual task conditions when we account for explicit awareness, and (3) aged adults demonstrate reduced learning when the primary task is accompanied with a secondary task, even when explicit awareness is included as a covariate in the analysis. These findings point to implicit learning deficits under dual task conditions that can be related to cognitive aging, demonstrating the need for sufficient cognitive resources while performing a sequence learning task.